The Influence Of Service Innovation And Promotional Strategies On Grab User Retention: The Mediating Role Of Purchase Decisions - Lukman Priyo Sembodo; David Sukardi Kodrat; Eric Harianto (UNIVERSITAS PAKUAN, 2026)
Grab, as one of the largest on-demand service providers in Southeast Asia, faces challenges in maintaining user loyalty amid intense competition with Gojek and similar platforms. Efforts to retain customers require both service innovation and effective promotional strategies, which play a role in shaping purchase decisions. This study aims to examine the relationship between service innovation and promotional strategies on Grab user retention, with purchase decisions serving as a mediating variable, using the Stimulus-Organism-Response (S-O-R) conceptual model. A quantitative approach was applied through a survey of 384 respondents who were active in the past six months, determined using Cochran’s formula with proportional random sampling. Data were collected using a five-point Likert scale questionnaire and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The study’s findings indicate that service innovation and promotional strategies have a positive and significant effect on purchase decisions, which in turn mediate their influence on user retention. These results contribute to the development of digital marketing literature while providing practical recommendations for Grab in designing more effective and sustainable service and promotional strategies.